(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
When used in dentistry, local anesthesia involves the injection of an anesthetic solution adjacent to the nerves that provide sensation to a region of the oral cavity where treatment will be delivered. The anesthetic solution temporarily prevents the propagation of nociceptive nerve impulses, thus allowing for the pain-free delivery of dental treatment. This activity reviews the indications, contraindications, anatomical considerations, equipment, techniques, and complications of local anesthesia in dentistry and highlights the dental team’s role in the safe and efficient delivery of local anesthesia.